2022
DOI: 10.1155/2022/9018939
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Digestive Endoscope Based on Artificial Intelligence System in Diagnosing Early Esophageal Carcinoma

Abstract: Objective. To explore the efficacy of digestive endoscopy (DEN) based on artificial intelligence (AI) system in diagnosing early esophageal carcinoma. Methods. The clinical data of 300 patients with suspected esophageal carcinoma treated in our hospital from January 2018 to January 2020 were retrospectively analyzed; among them, 198 were diagnosed with esophageal carcinoma after pathological examination, and 102 had benign esophageal lesion. An AI system based on convolutional neural network (CNN) was adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Finally, 19 papers relating to AI‐assisted diagnosis of early EC and its invasion depth were included in the study. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 By analyzing endoscopic WLI/NBI, the sensitivity and specificity of AI‐assisted systems, novices, and experts in the diagnosis of early EC and its infiltration depth were compared in these studies, respectively. The literature search process is shown in Figure 1 , and the basic information of each study was extracted (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 19 papers relating to AI‐assisted diagnosis of early EC and its invasion depth were included in the study. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 By analyzing endoscopic WLI/NBI, the sensitivity and specificity of AI‐assisted systems, novices, and experts in the diagnosis of early EC and its infiltration depth were compared in these studies, respectively. The literature search process is shown in Figure 1 , and the basic information of each study was extracted (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, after reading through the full text of 178 publications, 159 were further excluded (reviews [49], detailed data were not provided [69], the number of people included in the study was less than 10 [28], and meta‐analysis [13]). Finally, 19 papers relating to AI‐assisted diagnosis of early EC and its invasion depth were included in the study 6–24 . By analyzing endoscopic WLI/NBI, the sensitivity and specificity of AI‐assisted systems, novices, and experts in the diagnosis of early EC and its infiltration depth were compared in these studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eld of early detection of EC, different imaging modalities such as gastroscopy, WLI, and narrow-band imaging (NBI) have been used in various studies (19)(20)(21). A review of the literature showed that WLI images were used in 35% of studies (11,17,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), followed by a combination of WLI and NBI images in 10% (18, 23,34,35), CT images in 13% (36-39), NBI images in 3% (40), images of other modalities in 13% (41)(42)(43)(44), and the type of imaging was not mentioned in 26% of studies (Fig. 4) (32,42,(45)(46)(47)(48)(49)(50).…”
Section: Ec Image Segmentationmentioning
confidence: 99%
“…Of the 15 studies reviewed, 11 employed various CNN algorithms for both segmentation and classi cation. The remaining 4 studies utilized other ML algorithms, including 2 studies of the MTL algorithm (26, 32), one study of the Neuro-T algorithm(25), and one study that used Google Net and TensorFlow algorithms(41). Among the studies, the highest accuracy was achieved by Wu et al(24) with a value of 96.28%, utilizing the Faster-RCNN and DSN algorithms for segmentation and classi cation.…”
mentioning
confidence: 99%